1978
DOI: 10.1111/j.1365-246x.1978.tb03752.x
|View full text |Cite
|
Sign up to set email alerts
|

An optimal complex AR.MA model of the Chandler wobble

Abstract: summary. The character of the Chandler wobble suggests that the optimal representation of the observed polar motion is a complex AR.MA model. This paper develops the theory of such a model and presents a modification of the scalar AR.MA computer program of Akaike, Arahata & Ozaki. The complex AR.MA model is applied to the ILS data covering the period 1900–1975. An optimal AR.MA (1,4) model is obtained. The model parameters are interpreted to give a Chandler frequency of 0.8400 ± 0.0039 cpy a Q value of 50 < Q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…In fact, the variability of the CW frequency has been a subject of debate. Some authors assumed or proved the frequency to be invariant (e.g., Ooe 1978;Kuehne and Wilson 1996;Vicente and Wilson 1997;Gross et al 2003;Liao et al 2003;Seitz et al 2004). Some authors suggested a variable frequency (e.g., Melchior 1954Melchior , 1957Sekiguchi 1972Sekiguchi , 1976Guinot 1972;Carter 1981;Nastula et al 1993;Liu et al 2000;Schuh et al 2001;Höpfner 2003Höpfner , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the variability of the CW frequency has been a subject of debate. Some authors assumed or proved the frequency to be invariant (e.g., Ooe 1978;Kuehne and Wilson 1996;Vicente and Wilson 1997;Gross et al 2003;Liao et al 2003;Seitz et al 2004). Some authors suggested a variable frequency (e.g., Melchior 1954Melchior , 1957Sekiguchi 1972Sekiguchi , 1976Guinot 1972;Carter 1981;Nastula et al 1993;Liu et al 2000;Schuh et al 2001;Höpfner 2003Höpfner , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of any knowledge of its excitation, statistical models of the excitation can be adopted (e.g., Jeffreys, 1972;Ooe, 1978;Wilson and Haubrich, 1976;Wilson andVicente, 1980, 1990). In the absence of any knowledge of its excitation, statistical models of the excitation can be adopted (e.g., Jeffreys, 1972;Ooe, 1978;Wilson and Haubrich, 1976;Wilson andVicente, 1980, 1990).…”
Section: The Chandler Wobble and Its Excitationmentioning
confidence: 99%
“…Jeffreys (1958) and Smith and Dahlen (1981) noted that the Chandler wobble provides a probe of the anelastic properties of the Earth at a period (~435 days) far removed from the seismic frequencies that are commonly employed to determine the structure and rheological properties of the Earth. Recent determinations of the Q of the Chandler wobble using classical observations are in the range of 50-400 (Jeffreys, 1968;Currie, 1974Currie, , 1975Wilson and Haubrich, 1976;Ooe, 1978). A full exploitation of the geophysical information provided by the motion of the Earth will require an accurate determination of the excitation mechanism(s).…”
Section: E Polar Motionmentioning
confidence: 99%